Competence in High Performance Computing 2010 Proceedings of an International Conference on Competence in High Performance Computing, June 2010, Schloss Schwetzingen, Germany - Bischof, Christian; Hegering, Heinz-Gerd.; Nagel, Wolfgang E.; Wittum, Gabriel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents the state-of-the-art in simulation on supercomputers. Leading researchers present results achieved on systems of the Gauss-Allianz, the association of High-Performance Computing centers in Germany. The reports cover all fields of computational science and engineering, ranging from CFD to Computational Physics and Biology to Computer Science, with a special emphasis on industrially relevant applications. Presenting results for large-scale parallel microprocessor-based systems and GPU and FPGA-supported systems, the book makes it possible to compare the performance levels and usability of various architectures. Its outstanding results in achieving the highest performance for production codes are of particular interest for both scientists and engineers. The book includes a wealth of color illustrations and tables.
Keywords: Computer science; Electronic data processing; Computer simulation; Computer science -- Mathematics; Computer Science; Numeric Computing; Simulation and Modeling; Computational Science and Engineering; Computational Mathematics and Numerical Analysis